Targeting the link between late pregnancy and breast cancer - Chakravarthi, Balabhadrapatruni VSK (eLife Sciences Publications, Ltd, 2013)
Why does a first pregnancy after age 35 increase the risk of breast cancer, and what can be done to combat this?